PERAN PEMERINTAH DESA DALAM PEMBERDAYAAN MASYARAKAT DI DESATAPUNG JAYA KECAMATAN TANDUN KABUPATEN ROKAN HULU TAHUN 2021 - Sepnanda, Alpin Taufia; ,, Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The village government plays a role in facilitating the community and providing appropriate guidance regarding the development and empowerment objectives to be implemented. The community contributes ideas, energy, and even material resources to ensure the success of empowerment and development. The village government plays a role in implementing community empowerment activities. An example of this empowerment is goat farming. The problem in this research is the suboptimal performance of the Tapung Jaya village government in carrying out its role as a village government. The purpose of this study was to determine the role of the Tapung Jaya village government in optimizing the village community empowerment program through goat farming and to identify the supporting and inhibiting factors in implementing its role as a village government. This study refers to the theory of the role of village government according to Isbandi Rukmianto (2013), namely community empowerment through the Preparation Stage, Assessment Stage, Alternative Planning Stage, Action Plan Formalization Stage, Implementation Stage, Evaluation Stage, and Termination Stage. This research is a descriptive qualitative study with primary and secondary data sources. Data collection techniques used were interviews and documentation. Data analysis techniques were Data Reduction, Data Presentation, and Conclusion Drawing. The results of this study indicate that the role of the Tapung Jaya village government as the main driver in community empowerment activities in Tapung Jaya Village is not optimal, such as the lack of funds and other infrastructure such as skills training, participation, unclear goat farming management, and the existence of inhibiting factors in implementing the government's role in Tapung Jaya Village, Tandun District, Rokan Hulu Regency. Keywords: Community Empowerment, Preparation, Assessment, Implementation, and Evaluation.